Condition of the prooxidant-antioxidant system of some strains of Basidiomycetes - O. V. Fedotov (Regulatory Mechanisms in Biosystems, 2017)
The article deals with the calculation and comparison indications of the condition of the prooxidant-antioxidant system (PAS) of strains of Basidiomycetes under periodic surface cultivation on a glucose-peptone medium. The research material consisted of the mycelium and culture filtrate (CF) from 57 strains, 52 of them belonging to 7 species of the order Agaricales and 5 belonging to 5 species of the order Polyporales. The intensity of the processes of lipid peroxidation was determined by a modified spectrophotometric method for contents of active products to thiobarbituric acid. Total antioxidant activity (АОА) of the mycological material was evaluated by intensity of inhibition from accumulated products of lipid peroxide oxidation (LPO) in a model reaction of oxidation by Twin-80 oxygen of the air. From the data obtained, indicators of prooxidant activity (POA), indicators of reserve of substrate peroxidation (SPO) and the balance coefficient of the prooxidant-antioxidant system (CbPАS) were calculated. It was established that strains of Basidiomycetes are characterized by significant predominance of prooxidant activity characteristic of PAS in the culture filtrate in comparison with the mycelium indicator. The highest values of POA in the Culture Filtrate were observed on the 12-th day of cultivation for the strain Р-089 genus Pleurotus and strain Gl-2 genus Ganoderma, and for the mycelium on the 9-th day of cultivation for the strains Р-сіtr, Р-089, Р-er and Р-082 of the genus Pleurotus. There is a direct dependence between the indicators of POA in the CF and mycelium for each strain, this dependence and level of indication do not reflect their systematic placement. We distinguished a more significant prevalence of indicators of reserve of substrates peroxidation of mycelium for most strains, than for such indicators with CF The highest value of reserve SPO of mycelium was recorded for strains Р-447, Р-998, Р-039, Р-94, Р-2175, Р-сіtr, Р-er, D-140 of the genus Pleurotus and strains F-107, F-610 of the genus Flammulina. For the majority of the strains there was a clear prevalence of the values of the balance coefficients for PAS of mycelium over those of CF. Maximum values of the balance coefficient PAS of mycelium on the 9-th day were recorded for strains Т-10 (F. fomentarius) and D-140, Р-035, Р-01, Р-105 (P. ostreatus) and on the 12-th day for strains Sc-10 (S. commune), Р-kl, Р-14 (P. ostreatus), Р-er (P. eryngii) і 960 (A. cylindracea). The abovementioned strains are distinguished by the with high level of AOA in the mycelium on certain days of cultivation and can be recommended as producers of antioxidants of fungal origin.